PENGARUH SERTIFIKASI HALAL DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG DI MOOI CAKES CABANG TELANAI KOTA JAMBI - Widya Maharani Jayusman; Sucipto; Achyat Budianto (JSE: Jurnal Sharia Economica, 2026)
This study analyzes the effect of halal certification and product quality on consumer repurchase intention at Mooi Cakes, Telanai Branch, Jambi City. Using a quantitative approach, data were gathered via questionnaires from 100 respondents using accidental sampling and processed via IBM SPSS. Regression analysis shows that partially, halal certification has no significant effect on repurchase intention (t count 1.603 < t table 1.984). Conversely, product quality exerts a positive and significant partial effect t 6.764 p < 0.001), indicating that higher product quality directly stimulates repurchase intensity. Simultaneously, both variables significantly influence repurchase intention (F 35.681). The Adjusted R Square of 0.424 shows these variables explain 42.4% of the variance, while 57.6% is driven by outside factors. This study confirms product quality as the primary determinant driving consumer repurchase behaviour.